Analisis Strategi Pengembangan Produk Crunchy Martabite Dengan Pendekatan Business Model Canvas (BMC) - Wulan Dewi Siti Khotimah; Didit Purnomo (Universitas Muhammadiyah Surakarta, 2025)
This research is motivated by the increasingly rapid development of the culinary industry in Indonesia, as well as the emergence of product innovations such as Crunchy Martabite, a dry martabak variant that offers practicality, crunchy texture and a longer shelf life than traditional martabak. The aim of this research is to analyze the Crunchy Martabite product development strategy using the Business Model Canvas (BMC) approach, so that it can help MSMEs in designing and improving their business models amidst intense culinary market competition. The method used in this research is descriptive qualitative with a Participatory Action Research (PAR) approach. This approach involves direct participation of students and stakeholders in data collection and evaluation of business strategies. The research results show that nine BMC elements ranging from customer segments to cost structure play an important role in identifying business strengths and weaknesses, so that they can help optimize product development and marketing strategies. These findings support the use of BMC as an effective tool in developing innovation and competitiveness of culinary MSMEs.